2021
DOI: 10.3390/cancers13143379
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Skills and Technological Advancements to Avoid Complications in Lateral Neck Dissection for Differentiated Thyroid Cancer

Abstract: Neck dissection is a surgical procedure reserved for thyroid cancer cases with clinically evident lymphatic invasion. Although neck dissection is a reliable and safe procedure, it can determine a significant morbidity involving a variety of structures of nervous, vascular and endocrine typology. A careful pre-operative study is therefore essential to better plan surgery. Surgical experience, combined with accurate surgical preparation and merged with adequate and specific techniques, can certainly help reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Therefore, providing optimal choices of surgical strategies for LATC patients to further increase the resection rate, reduce surgical risks, decrease the incidence of postoperative complications and mortality, and safeguard the quality of life while prolonging survival as much as possible are the current hotspots of controversy and the direction of endeavor. However, it is worth noting that the current editions of academic guidelines [ 3 , [32] , [33] , [34] ] for the surgical treatment of LATC emphasise the weighing of the surgical benefit-risk ratio, i.e., the need for the surgeon to weigh radical versus palliative tumor-reducing treatments. However, there is still a lack of convincing evidence in terms of comparing the assessment of the efficacy benefits of different treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, providing optimal choices of surgical strategies for LATC patients to further increase the resection rate, reduce surgical risks, decrease the incidence of postoperative complications and mortality, and safeguard the quality of life while prolonging survival as much as possible are the current hotspots of controversy and the direction of endeavor. However, it is worth noting that the current editions of academic guidelines [ 3 , [32] , [33] , [34] ] for the surgical treatment of LATC emphasise the weighing of the surgical benefit-risk ratio, i.e., the need for the surgeon to weigh radical versus palliative tumor-reducing treatments. However, there is still a lack of convincing evidence in terms of comparing the assessment of the efficacy benefits of different treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the available evidence, the data obtained show that electrophysiological monitoring of the recurrent nerve is not yet a routine practice due to the recent acquisition and indication in a limited number of cases. In particular, the association of electrophysiological monitoring with direct visualization of nerve structures in cases at higher risk (reoperations, oncological surgery, and approach to voluminous goiters) represents the gold standard for the prevention of iatrogenic lesions of the recurrent nerve [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…If there was no obvious lymph or chylous exudation in the inferior carotid sheath area under observation for at least 1 min, the operation was finished. If there was obvious lymph of chylous exudation during observation, we mainly ligated the injured duct and its tributaries using a running suture (5-0 Prolene) without any other tissue for additional covering [ 11 13 ] until the exudation stopped as a conventional method. We found that some patients still had LL/CL after surgery.…”
Section: Methodsmentioning
confidence: 99%